2013
DOI: 10.3109/02713683.2012.757323
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dry Eye Therapy Under Conditions of Environmental Stress

Abstract: Purpose: Dry eye is often characterized by increased tear evaporation due to poor tear film quality, especially of the lipid component of the tear film. Using an environmental chamber to induce environmental stress, this study compared the effect of three lubricant eye drops on various aspects of tear physiology in a crossover design (evaporation was the principal outcome measure). Methods: Three eye drop formulas were tested: 0.5% carmellose sodium (Drop C), 0.5% carmellose sodium with added lipid (Drop C-L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…In a direct comparison of the lipidcontaining formula ADV2 with an aqueous-only eye drop, a similar reduction in dry eye symptoms was reported, but with a greater reduction in tear film evaporation after 2 weeks of dosing, 24 suggesting that the formulation of ADV2, with a reduced lipid content for improving tolerability while maintaining the benefits of the lipid, was effective. Those findings are consistent with the results from the present study demonstrating improvements in all groups in TBUT, a marker of tear film stability that may directly relate to Table I for treatment and formulation information.…”
Section: Discussionmentioning
confidence: 66%
“…In a direct comparison of the lipidcontaining formula ADV2 with an aqueous-only eye drop, a similar reduction in dry eye symptoms was reported, but with a greater reduction in tear film evaporation after 2 weeks of dosing, 24 suggesting that the formulation of ADV2, with a reduced lipid content for improving tolerability while maintaining the benefits of the lipid, was effective. Those findings are consistent with the results from the present study demonstrating improvements in all groups in TBUT, a marker of tear film stability that may directly relate to Table I for treatment and formulation information.…”
Section: Discussionmentioning
confidence: 66%
“…Twenty trials were reported as being double-masked (Baeyens 2012; Bron 1998a; Christensen 2009; Cohen 2014; Johnson 2008; Nelson 1988; Tomlinson 2013), single-masked (Foley-Nolan 1995), masked (Simmons 2007), masked-observer (Lee 2011) or investigator-masked trials (Aguilar 2014; Benelli 2010; Brodwall 1997; Bron 1998b; Donshik 1998 Trial 2; Donshik 1998 Trial 3; Khanal 2007; Kislan 2008; Simmons 2004a; Xiao 2008), but insufficient details were provided as to how masking was performed. Iester 2000 did not report masking.…”
Section: Resultsmentioning
confidence: 99%
“…Allergan funded a project studying the efficacy of Refresh Tears ® , Refresh Ultra ® , and Refresh Optive ® in relieving the signs and symptoms of dry eye 43. A total of 37 participants completed the study; 18 with a history of dry eye and 19 controls without a history of dry eye.…”
Section: Resultsmentioning
confidence: 99%